Once a spy - Thomson, Keith (New York : Anchor Books, 2011)
When Charlie Clark takes a break from his latest losing streak at the track to bring home his Alzheimer's-addled father, Drummond, they're attacked by two mysterious shooters. At first, Charlie thinks his Russian 'creditors' are employing aggressive collection tactics. But once Drummond effortlessly hot-wires a car, Charlie discovers that his father was a deep cover CIA agent--and extremely sensitive information is rattling around in his mind that the CIA wants 'contained'.
Includes excerpt from: Twice a spy.
Keywords: United States. -- Central Intelligence Agency -- Fiction; Gambling -- Fiction; Gamblers -- Fiction; Alzheimer's disease -- Patients -- Fiction; Fathers and sons -- Fiction